Modelo assistencial para captação, diagnostico e seguimento de pacientes com asma em unidades básicas de saúde - Leal, Renata Cristina de Angelo Calsaverini (2011)
Asthma is a chronic inflammatory disease characterized by hyperresponsiveness of the lower airways and variable limitation of airflow. Severity is classified according to the frequency, intensity of symptoms and lung function. Asthma accounts for high rates of mortality and morbidity. It constitutes a public health issue that mobilizes actions of Brazilian scientific societies and local government officials . Part of these activities aimed at controlling mild to moderate asthma for care optimization to patients with the disease in the primary care. Objectives: To characterize the Basic Health Units (BHU) of Sao Jose do Rio Preto (BHU), considering their demographic profile, attendance flow, physical space, professional and management attendance; aiming to propose a health assistance model for treating patients with asthma. Material and Method: This was a descriptive study, linked to the Medical School of Sao Jose do Rio Preto (FAMERP), and performed along with the Municipal Health Service of São José do Rio Preto. The variables were collected by means of questionnaires; data collection from the municipal and state systems of information, photos, bibliographical surveys and analysis of the technical standards of health official systems. Data were shown by means of tables, charts, flowcharts and photograph; descriptive statistical analyses were used to interpret them for applying randomly the variables, through which the averages were calculated for discrete data. T test was used to compare variables for independent observation with the significance of 5% Results: There was a predominance of the emergency service for asthmatic patients, lack of registration based on the International Classification of Diseases (ICD) in the HBUs and hospitalizations. No structure for accommodating patients with mild and moderate asthma in the primary care was observed, as well as no correlation between the proposed health promotion program and a structured program provided for patients with mild and moderate asthma in these services. Based on these assumptions, a specific assistance model was developed for asthma care in the primary health care services. Conclusion: There is a lack of specific registration and care of asthmatic patients in the municipal pilot-units. This may be attributed to the difficulty of involvement of the multidisciplinary teams in relation to the present proposal of the Health System. The proposal of an ideal model of care follows a system that manages professional training, the standardization of attendance flow towards different levels of care, dispensing medications and suiting physical-environmental settings.